2009
DOI: 10.1002/bsl.864
|View full text |Cite
|
Sign up to set email alerts
|

Arresting and convicting the innocent: the potential role of an “inappropriate” emotional display in the accused

Abstract: Research from both simulated and actual jurors has demonstrated that the defendant's emotional display can influence legal decisions. The purpose of this paper is to review the evidence regarding the influence of the defendant's emotional display, and to consider the potential role of suspect and defendant emotion in wrongful convictions. It is possible that the lack of "appropriate" emotion during questioning or interrogation may lead investigators to create a mind-set that the suspect is the guilty party; as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 70 publications
0
35
0
2
Order By: Relevance
“…It is widely assumed that emotions play a critical part in the judicial process (Feigenson, 2010;Heath, 2009;Levenson, 2008), an assumption that is present in the very foundations of the U.S. court system. According to the Sixth Amendment of the U.S. Constitution, for example, face-to-face confrontation "permits the jury … to observe the demeanor of the witness in making his statement, thus aiding the jury in assessing his credibility."…”
Section: The Emotional Child Witness: Effects On Juror Decision-makingmentioning
confidence: 99%
“…It is widely assumed that emotions play a critical part in the judicial process (Feigenson, 2010;Heath, 2009;Levenson, 2008), an assumption that is present in the very foundations of the U.S. court system. According to the Sixth Amendment of the U.S. Constitution, for example, face-to-face confrontation "permits the jury … to observe the demeanor of the witness in making his statement, thus aiding the jury in assessing his credibility."…”
Section: The Emotional Child Witness: Effects On Juror Decision-makingmentioning
confidence: 99%
“…However, a recent review of the evidence from real court cases and the laboratory suggests that the emotions displayed during interrogation or during the court hearings affect judgments of the credibility of the defendant as well (Heath, 2009). For example, Heath et al (2004) found that the level of emotional arousal (low, moderate and high) expressed by a defendant influenced the verdict under conditions of weak technical evidence; however, in this study the female defendant was impersonated by a female actress.…”
Section: Introductionmentioning
confidence: 97%
“…The results of the recent studies highlight the importance of the emotional expression accompanying witness statements for the perceived credibility of adult victims of violence and abuse (Baldry & Winkel, 1998;Bornstein & Wiener, 2009;Kaufmann, Drevland, Wessel, Overskeid, & Magnussen, 2003;Maroney, 2006;Nadler & Rose, 2003;Zammuner, 2000), and possibly for witnesses in general (Ask & Lanström, 2010;Heath, 2009;Heath, Granneman, & Peacock, 2004;Wessel, Bollingmo, Sønsteby, Nielsen, Eilertsen, & Magnussen, 2012), suggesting that judgments of credibility are based on social stereotypes of appropriate behavior of individuals in such positions (Klippenstein & Schuller, 2012;Tsoudis & Smith-Lovin, 1998;Wessel et al, 2012). In line with the studies cited above, a series of experiments from our laboratory, investigating the relationship between expressed emotions and perceived credibility of a rape victim (reviewed by Magnussen & Wessel, 2010), show that when a female victim displays negative emotions-sadness and despair-she is perceived more credible than when she is emotionally neutral or showing a nervously smiling, positive reaction, even if all of these emotional reactions are normal and represented in actual police interviews with rape victims (Magnussen & Wessel, 2010).…”
mentioning
confidence: 92%